2012
DOI: 10.1111/aas.12001
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome: nationwide changes in incidence, treatment and mortality over 23 years

Abstract: The incidence of ARDS has almost doubled, but hospital mortality has decreased during the 23 years of observation. The 10-year survival of ARDS survivors is poor compared with the reference population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 25 publications
6
67
1
2
Order By: Relevance
“…Although the overall survival rate is improving [9,10], there is a notable difference when considering in-hospital mortality over several observational studies [2][3][4][8][9][10][11]. This may be explained by differences in risk factors, availability of diagnostics, ability to recognise ARDS and some selection biases affecting clinical trials [12].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the overall survival rate is improving [9,10], there is a notable difference when considering in-hospital mortality over several observational studies [2][3][4][8][9][10][11]. This may be explained by differences in risk factors, availability of diagnostics, ability to recognise ARDS and some selection biases affecting clinical trials [12].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…In fact, the incidence of ARDS ranges from 1.5 cases per 100 000 [2] to nearly 79 cases per 100 000 [3], with European countries reporting a lower incidence than USA [6]. Moreover, studies from Brazil reported incidence rates ranging from 1.8 to 31 per 100 000 [7,8].Although the overall survival rate is improving [9,10], there is a notable difference when considering in-hospital mortality over several observational studies [2][3][4][8][9][10][11]. This may be explained by differences in risk factors, availability of diagnostics, ability to recognise ARDS and some selection biases affecting clinical trials [12].…”
mentioning
confidence: 99%
“…17 Despite this improvement, however, data indicate broad differences between survival at hospital discharge Drs Chiumello, and Gotti are affiliated with the Dipartimento di Anestesia e Rianimazione (Intensiva e Subintensiva) e Terapia del dolore, Fondazione IRCCS Ca' Granda-Ospedale Maggiore Policlinico, Milano, Italy. Drs Chiumello, Coppola, and Froio are affiliated with the Dipartimento di Fisiopatologia Medico-Chirurgica e dei Trapianti, Università degli Studi di Milano, Italy.…”
Section: Long-term Mortalityunclassified
“…[10][11][12] However, patients who survive ARDS remain at risk for mortality and may have persistent morbidity. [13][14][15][16][17][18] This article will review the long-term outcomes after ARDS, focusing on mortality, health-related quality of life (HRQOL), neuropsychological disability, radiological findings, and pulmonary dysfunction (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The most common risk factors for developing ARDS can be grouped into direct (acute severe pneumonia, aspiration of gastric content) and indirect (sepsis, acute severe pancreatitis, massive blood component transfusion) effects (Galvin et al, 2011). The incidence of ARDS since 1990 has doubled (Sigurdsson et al, 2013), and the level of mortality can reach even 50% (Ferguson et al, 2007) in intensive care unit (ICU) patients. The treatment of these patients can be very complicated, and can include serious fluid management, feeding, extra corporal membrane oxygenation, and mechanical lung ventilation advanced techniques.…”
mentioning
confidence: 99%